2012
DOI: 10.2989/16085914.2012.723196
|View full text |Cite
|
Sign up to set email alerts
|

Comparative behavioural assessment of an established and a new tigerfishHydrocynus vittatuspopulation in two man-made lakes in the Limpopo River catchment, southern Africa

Abstract: With the continued establishment of man-made lakes within the natural distribution range of tigerfish in southern Africa, many artificial tigerfish populations now exist in the region. Very little of the behavioural ecology of these artificial but ecologically important populations is known. Letsibogo and Schroda man-made lakes are two such systems in the Limpopo River catchment. Currently, an established population of tigerfish occurs in Schroda, which is proposed to be used to establish another population in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…() from a boat between 21 June and 22 October 2016 (Table ). On capture, each fish was guided into a soft weighing sling before being lifted and placed in a 50 l aerated water‐filled container into which 2‐phenoxy‐ethanol, 0.3 ml l −1 , had been added as anaesthetic (O'Brien et al ., ). Once the fish was anaesthetised, it was moved into another 50 l aerated water container with circulating freshwater from the river to start the recovery process.…”
Section: Methodsmentioning
confidence: 97%
“…() from a boat between 21 June and 22 October 2016 (Table ). On capture, each fish was guided into a soft weighing sling before being lifted and placed in a 50 l aerated water‐filled container into which 2‐phenoxy‐ethanol, 0.3 ml l −1 , had been added as anaesthetic (O'Brien et al ., ). Once the fish was anaesthetised, it was moved into another 50 l aerated water container with circulating freshwater from the river to start the recovery process.…”
Section: Methodsmentioning
confidence: 97%
“…Fewer than 40 papers are available for African inland fish telemetry studies. Most recapture attempts were unsuccessful (Baras et al ., ; OʼBrien et al ., ). Mlewa et al .…”
Section: Details Of All Eels (Anguilla Spp) Radio Tagged In the Thukmentioning
confidence: 97%
“…Fewer than 40 papers are available for African inland fish telemetry studies. Most recapture attempts were unsuccessfulOʼBrien et al, 2012) Mlewa et al (2005). were the only researchers to observe live recapture of fishes (Lungfish, Protopterus spp.)…”
mentioning
confidence: 99%
“…Recently, O'Brien et al () characterized the feeding behaviour of the H. vittatus population in Schroda Dam and found that they demonstrated routine crepuscular, piscivorous feeding patterns. Active roaming movements in deep open water adjacent to well‐vegetated areas, or areas with structure in the limnetic zone along the periphery of Schroda, were associated with this feeding behaviour (O'Brien et al , ). During the day (0800 to 1600 hours) H. vittatus characteristically occupied deep sheltered areas where their activity decreased (O'Brien et al , ).…”
mentioning
confidence: 99%
“…Active roaming movements in deep open water adjacent to well‐vegetated areas, or areas with structure in the limnetic zone along the periphery of Schroda, were associated with this feeding behaviour (O'Brien et al , ). During the day (0800 to 1600 hours) H. vittatus characteristically occupied deep sheltered areas where their activity decreased (O'Brien et al , ). During a summer (February 2011) survey at least five radio‐tagged H. vittatus individuals displayed daily uncharacteristic increases in mid‐morning activity (0800 to 1200 hours).…”
mentioning
confidence: 99%